Transcriptome analyses of the cortex and white matter of focal cortical dysplasia type II: Insights into pathophysiology and tissue characterization - Assis-Mendonça, Guilherme Rossi; Athié, Maria Carolina Pedro; Tamanini, João Vitor Gerdulli; Souza, Arethusa de; Zanetti, Gabriel Gerardini; Araújo, Patrícia Aline Oliveira Ribeiro de Aguiar; Ghizoni, Enrico; Tedeschi, Helder; Alvim, Marina Koutsodontis Machado; Almeida, Vanessa Simão de; de Souza, Welliton; Coras, Roland; et al. (Frontiers in Neurology, 2023)
Introduction: Focal cortical dysplasia (FCD) is a common cause of pharmacoresistant epilepsy. According to the 2022 International League Against Epilepsy classification, FCD type II is characterized by dysmorphic neurons (IIa and IIb) and may be associated with balloon cells (IIb). We present a multicentric study to evaluate the transcriptomes of the gray and white matters of surgical FCD type II specimens. We aimed to contribute to pathophysiology and tissue characterization. Methods: We investigated FCD II (a and b) and control samples by performing RNA-sequencing followed by immunohistochemical validation employing digital analyses. Results: We found 342 and 399 transcripts differentially expressed in the gray matter of IIa and IIb lesions compared to controls, respectively. Cholesterol biosynthesis was among the main enriched cellular pathways in both IIa and IIb gray matter. Particularly, the genes HMGCS1, HMGCR, and SQLE were upregulated in both type II groups. We also found 12 differentially expressed genes when comparing transcriptomes of IIa and IIb lesions. Only 1 transcript (MTRNR2L12) was significantly upregulated in FCD IIa. The white matter in IIa and IIb lesions showed 2 and 24 transcripts differentially expressed, respectively, compared to controls. No enriched cellular pathways were detected. GPNMB, not previously described in FCD samples, was upregulated in IIb compared to IIa and control groups. Upregulations of cholesterol biosynthesis enzymes and GPNMB genes in FCD groups were immunohistochemically validated. Such enzymes were mainly detected in both dysmorphic and normal neurons, whereas GPNMB was observed only in balloon cells. Discussion: Overall, our study contributed to identifying cortical enrichment of cholesterol biosynthesis in FCD type II, which may correspond to a neuroprotective response to seizures. Moreover, specific analyses in either the gray or the white matter revealed upregulations of MTRNR2L12 and GPNMB, which might be potential neuropathological biomarkers of a cortex chronically exposed to seizures and of balloon cells, respectively.
CRIS-Team Scopus Importer:2023-04-07
Keywords: cholesterol biosynthesis enzymes; focal cortical dysplasia; GPNMB; humanin-like 12; immunohistochemistry; molecular biomarker; transcriptome